G215(P) Improving safety at the very beginning: a novel neonatal delivery safety checklist. (12th March 2018) - Taylor, AM; Lewis, P; Nugent, M; Montague, J; Mitra, S
Abstract : Aim: Resuscitation and stabilisation of newborn babies can be a complex process involving members of several multi-disciplinary teams. We aimed to improve early newborn care by reducing errors and improving safety at each stage of this process. The World Health Organisation (WHO) Surgical Safety Checklist 1, 2 has been shown to dramatically reduce morbidity and mortality in surgical patients. Using the same principles, we created a novel Neonatal Delivery Safety Checklist with an aim to improve multi-disciplinary communication and early care of the newborn. Method: We started by surveying all members of the multi-disciplinary team about their experiences of attending complex and preterm deliveries. We process mapped the stages involved in attending a delivery and combined this with the survey information. This formed the basis of the pilot project where, as in the WHO Surgical Safety Checklist, we identified three 'vital phases': a preparatory period; a pause before the delivery where the whole team is encouraged to answer the question 'are we ready?'; and before transfer to the neonatal unit. Results: We piloted the checklist over two weeks and immediate feedback was gathered. A 'plan, do, study, act' cycle was then initiated to respond to feedback from the multi-disciplinary team. As a result, the Checklist has gone through seven variations to date to make it as user friendly as possible whilst retaining the key principles. Admission temperature in babies born at <32 weeks has shown a dramatic improvement since The Checklist has been introduced for routine preterm deliveries. Nearly 50% of infants had admission temperature <36.5°C in the month prior to The Checklist being introduced (June 2017) compared with 12.5% 2 months afterwards (September 2017). Staff satisfaction regarding intra- and inter-disciplinary communication has anecdotally improved and is currently being formally assessed. Conclusion: Our novel Neonatal Delivery Safety Checklist has improved early care of the newborn, including admission temperature of preterm babies. References: . World Health Organisation. Safe surgery saves lives frequently asked questions 2014. http://www.who.int/patientsafety/safesurgery/faq_introduction/en/ (Accessed: 7th September 2017) . Haynes A, et al . For the safe surgery saves lives study group. N Engl J Med2009;360:491–49.